1988
DOI: 10.1002/1097-0142(19880901)62:5<895::aid-cncr2820620508>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors influencing survival in combined radiotherapy and surgery of squamous cell carcinoma of the esophagus with special reference to a histopathologic grading system

Abstract: Sixty-six patients with squamous cell carcinoma of the esophagus were treated with combined surgery and radiotherapy, mostly in a sandwich fashion. Fourteen patients received misonidazole during preoperative radiotherapy. Prospective cumulative survival at 1, 2, and 5 years was 60%, 35%, and 17%, respectively. Original biopsy specimens and operation specimens were evaluated according to a histopathologic grading system based on an evaluation of the tumor cell population in terms of cell differentiation, struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Previous literature has confirmed that invasive front grading, in contrast to Broder and Bryne's grading, is of high prognostic value, because of the following reasons: (a) tumors often are more poorly differentiated in invasive parts compared to superficial parts; (b) blood group H antigen is often lost in invasive tumor margins of OSCC, and this loss is associated with poor prognosis; (c) the increased expression of proliferation‐associated structures in the invading tumor front; (d) melanoma cells from deep tumor parts have a higher DNA content than more superficial cells; (e) the increased expression of Ki‐67, L‐myc, c‐myc, N‐myc, and c‐erbB‐2 oncoproteins in most invasive lung cancers; and (f) the increased labeling of bromodeoxyuridine at the site of invasion …”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has confirmed that invasive front grading, in contrast to Broder and Bryne's grading, is of high prognostic value, because of the following reasons: (a) tumors often are more poorly differentiated in invasive parts compared to superficial parts; (b) blood group H antigen is often lost in invasive tumor margins of OSCC, and this loss is associated with poor prognosis; (c) the increased expression of proliferation‐associated structures in the invading tumor front; (d) melanoma cells from deep tumor parts have a higher DNA content than more superficial cells; (e) the increased expression of Ki‐67, L‐myc, c‐myc, N‐myc, and c‐erbB‐2 oncoproteins in most invasive lung cancers; and (f) the increased labeling of bromodeoxyuridine at the site of invasion …”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy has been of little value in converting unresectable cancers into resectable ones (30). However, it decreases the incidence of locoregional recurrence (31). A recently published article showed a signi cant survival advantage with postoperative chemoradiation therapy for lymph-node-positive esophageal carcinoma (32).…”
Section: Radiotherapymentioning
confidence: 99%
“…Patients with well (GI) or moderately (GII) differentiated tumours classified as stage 0, I, IIA and IIB, III respectively did not show a significant better survival than patients with poorly differentiated (GIII) tumours (Fig 4). 20 columnar epithelium occurred in the lower oesore 2: Survival ofresected patients without regional lymph node metastases (n=61) versus phagus, secondary to gastro-oesophageal reflux.3 nts with regional lymph node metastases (n=20).…”
Section: Pathological Findings and Stagingmentioning
confidence: 99%